2021
DOI: 10.3390/pr9020362
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Degradation of Nontuberculous Mycobacteria Formed on Stainless Steel Following Treatment with Immortelle (Helichrysum italicum) and Common Juniper (Juniperus communis) Essential Oils

Abstract: Nontuberculous mycobacteria, like other opportunistic premise plumbing pathogens, produce resistant biofilms on various surfaces in the plumbing system including pipes, tanks, and fittings. Since standard methods of water disinfection are ineffective in eradicating biofilms, research into new agents is necessary. Essential oils (EOs) have great potential as anti-biofilm agents. Therefore, the purpose of this research was to investigate the potential anti-biofilm effect of common juniper (Juniperus communis) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The use of essential oils of J. communis from the whole plant (leaves and branches) has been shown to have a temperature-dependent growth-inhibitory effect (MIC) for bacteria of the genus Mycobacterium , at concentrations between 0.8 and 3.2 mg/mL. Although the use of subinhibitory concentrations allows limiting the formation of biofilms by up to 49% after 3 days [ 98 ], its combination with essential oils extracted from Helichrysum italicum has been shown to have synergistic activity, allowing the concentrations used to be reduced 3-fold to achieve similar effects [ 97 ]. It has also been observed that the use of essential oils from J. communis berries is capable of reducing the adhesion of L. monocytogenes cells to HT-29 and HCT116 colon-cancer cells by 62%, thus reducing the capacity of this foodborne pathogen to cause intracellular infections by establishing favorable and competent unions with the host cells [ 93 ].…”
Section: Biological Potential Of Juniperus Communis ...mentioning
confidence: 99%
“…The use of essential oils of J. communis from the whole plant (leaves and branches) has been shown to have a temperature-dependent growth-inhibitory effect (MIC) for bacteria of the genus Mycobacterium , at concentrations between 0.8 and 3.2 mg/mL. Although the use of subinhibitory concentrations allows limiting the formation of biofilms by up to 49% after 3 days [ 98 ], its combination with essential oils extracted from Helichrysum italicum has been shown to have synergistic activity, allowing the concentrations used to be reduced 3-fold to achieve similar effects [ 97 ]. It has also been observed that the use of essential oils from J. communis berries is capable of reducing the adhesion of L. monocytogenes cells to HT-29 and HCT116 colon-cancer cells by 62%, thus reducing the capacity of this foodborne pathogen to cause intracellular infections by establishing favorable and competent unions with the host cells [ 93 ].…”
Section: Biological Potential Of Juniperus Communis ...mentioning
confidence: 99%
“…As previously described for the experiments, ATCC strains were used: Mycobacterium avium ssp. avium (serotype 2) ATCC 25291 (M. avium) and Mycobacterium intracellulare ATCC 13950 (M. intracellulare) [28][29][30][31]. Middlebrook 7H9 broth (7H9S, Difco, Detroit, MI, USA) with 10% albumin-dextrose-catalase enrichment (ADC, Biolife Italiana, Milano, Italy) and 0.05% Tween 80 (Tw 80, Biolife Italiana, Milano, Italy) was used for subcultivation of bacterial strains at 37 • C for at least 14 days to obtain 10 8 CFU mL −1 .…”
Section: Strains and Growth Mediamentioning
confidence: 99%
“…Peruč et al [4] investigated the biofilm degradation ability of Juniperus communis and Helichrysum italicum EOs against nontuberculous mycobacteria found in plumbing systems, including pipes, tanks, and fittings. They found that H. italicum EO showed the strongest biofilm degradation ability against tested strains.…”
mentioning
confidence: 99%